Minat Mahasiswa Akuntansi Menjadi Konsultan Pajak: Self Efficacy, Job Market, Penghargaan Finansial - Kadek Mita Putri Hildyanti; Sang Ayu Putu Arie Indraswarawati; I Wayan Budi Satriya (Hita Akuntansi dan Keuangan, 2026)
This study aims to investigate how confidence in abilities, job market conditions and monetary rewards influence on accounting students’ intention to pursue tax consultancy at Universitas Hindu Indonesia.  This research applied a survey approach, where information was gathered using questionnaires given to 210 accounting students, and the analytical method employed was multiple linear regression.  The findings reveal that self-confidence, labor market factors, and financial compensation exert a strong and meaningful influence on students’ aspirations to become tax consultants. The implications stress the need to enhance students’ confidence, supply accurate information about career prospects in taxation, and underscore the financial benefits of the tax consultant profession as strategies to raise students’ interest in entering this field.